Cross-cultural buyer behavior - Taylor, Charles R., 1961-; Lee, Doo-Hee (Advances in international marketing ;, 2007)
The theme of this issue is international buyer behavior. The papers collected in this volume contribute to theory development and contain important implications for managers and policy makers. With chapters written by leading marketing scholars from around the world, including current and/or former Presidents of the American Academy of Advertising, the European Academy of Advertising, and the Korea Advertising Society, this volume focuses on cutting edge issues that affect buyer behavior in an international context. The first of the four sections of the book focuses on a controversial topic: the impact of direct to consumer prescription drug advertising on consumers. Next is a group of papers that looks at the role of emotions in advertising and retailing contexts and their impact on buyers. The third section of the book examines cultural factors as they pertain to buyer behavior in multiple contexts, including explaining apparently paradoxical buyer behavior among Koreans and examining drivers of satisfaction with industrial goods across markets. The final set of chapters examines a truly hot topic in international buyer behavior research: interactive marketing in international contexts. Papers in these chapters examine current issues such as developing loyalty to on-line communities, reactions to mobile gaming and banner advertisements, and cross-national differences in website structure.